2015
DOI: 10.1155/2015/296186
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Antioxidant, Anti-Inflammatory, and Cytotoxic Activities of Propolis from the Stingless BeeTetragonisca fiebrigi(Jataí)

Abstract: Propolis from stingless bees Tetragonisca fiebrigi found in Brazil is used in folk medicine by their nutritional and therapeutic properties. However, there are no scientific records evidencing such properties. The present study was designed to investigate the chemical composition and the biological properties of propolis from T. fiebrigi. For this, the chemical composition of the ethanol extract of propolis (EEP) was determined by GC-MS and presented phenolic compounds, alcohol, and terpenes as its major class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 55 publications
1
109
0
8
Order By: Relevance
“…EEGP and its fractions had no bactericidal effects on CA-MRSA at the test concentrations (MIC > 1000 μg/mL). These results demonstrate that all of the samples were bactericidal agents (MIC/MBC ≤ 4), except for EAFGP (MBC/MIC = 40), according to French (2006 Campos et al (2015) found that the ethanolic extract of Tetragonisca fiebrigi geopropolis (known as Jataí) had antibacterial effects on two strains of S. aureus (MIC = 0.55-0.65 mg/mL and MBC ˃ 1000 µg/mL) and P. aeruginosa (MIC and MBC ˃ 1000 µg/mL). In these studies, it was suggested that prenylated benzophenones , diterpene kaurenoic acid (Velikova et al 2000), cinnamic acid (Campos et al 2015), and p-coumaric acid (Campos et al 2015) in the different types of geopropolis were responsible for their antibacterial properties.…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…EEGP and its fractions had no bactericidal effects on CA-MRSA at the test concentrations (MIC > 1000 μg/mL). These results demonstrate that all of the samples were bactericidal agents (MIC/MBC ≤ 4), except for EAFGP (MBC/MIC = 40), according to French (2006 Campos et al (2015) found that the ethanolic extract of Tetragonisca fiebrigi geopropolis (known as Jataí) had antibacterial effects on two strains of S. aureus (MIC = 0.55-0.65 mg/mL and MBC ˃ 1000 µg/mL) and P. aeruginosa (MIC and MBC ˃ 1000 µg/mL). In these studies, it was suggested that prenylated benzophenones , diterpene kaurenoic acid (Velikova et al 2000), cinnamic acid (Campos et al 2015), and p-coumaric acid (Campos et al 2015) in the different types of geopropolis were responsible for their antibacterial properties.…”
Section: Resultsmentioning
confidence: 62%
“…In our study, the amount of reducing compounds was much higher than that found by Souza et al (2013) in M. subnitida geopropolis from Paraiba state, Brazil (ranging from 25.6 ± 0.5 to 115.8 ± 0.8 µg GAE/mg). This suggests that the bee species and/or its habitat influence the chemical composition of geopropolis (Campos et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations